The impacts of social responsibility on the environmental sustainability performance of the Malaysian construction industry - W. A., Ajibike; Adeleke, A. Q.; Fazeeda, Mohamad; J.A., Bamgbade; T.D., Moshood (Taylor & Francis, 2021)
Properly harnessed social responsibility is vital for construction organization’s environmental sustainability as it provides are source for their competitive edge in construction project delivery. This study examines the impacts of social responsibility on Malaysian construction firms’ environmental sustainability performance. Across-sectional survey of 185 questionnaires was administered to respondents from Malaysian G7 construction firms. PLS path modelling out comes show that social responsibility and coercive pressure are positive predictors of environmental sustainability performance. The results also established that despite the charitable nature of social responsibility, construction firms are still obliged to be socially responsible through investment in environmental and social responsibility activities. This could result from conformity with guidelines that mandated them to spend on social responsibility activities and secure legitimacy from multiple stakeholders. Our results also reveal that coercive pressure transmits the positive effects of social responsibility on environmental sustainability performance. Thus, it was established that coercive pressure is a positive mediator and a facilitator that plays a complementary role between social responsibility and environmental sustainability performance. The implications and recommendations for future research are also discussed.